(untitled) (Al-Qamar, 2021)
Islam provides way to its followers in all aspects and activities of life, in economic values, social values as well as ethical values. Its basic guidance about the economics is mentioned in various verses of the Quran. Everyone knows that human livelihood is in constant progress, therefore, many problems of economics are arising day by day. The scholars continued to give fatwa in the light of the qur ’an and hadith in order to solve the problems of these economic issues. In this article, international Fiqh Academy Jeddah’s resolutions have been described in which daily economic problems have been resolved like zakat on depts, insurance and reinsurance, inflation and the Changing Value of Currency etc.